1991
DOI: 10.1111/j.1365-2303.1991.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology and Immunocytochemistry of Metastatic Melanoma

Abstract: The cytological and immunological findings of 81 metastatic melanomas are described. Fine needle aspiration was performed from secondary deposits in lymph nodes (38), subcutaneous and soft tissue (36), abdomen (5), lung (1) from 67 patients with histologically verified malignant melanoma. One patient had disease which had spread into the cerebrospinal fluid. Cytomorphologically the cases were classified as classical (47%), carcinoma-like (22%), spindle cell type (14%), lymphoma like (6%), undifferentiated (6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 2 publications
6
60
0
Order By: Relevance
“…The frequency of each feature in melanoma was reported to be approximately 50%. 5,7,10,12,13 We found that these features were noted less frequently in the spindle cell melanomas (22%, 35%, and 22%, respectively), and 7 of the current study cases (9%) failed to exhibit any of the characteristic features. In addition, the cells of spindle cell melanoma tended to form cohesive microtissue fragments with a fascicular or storiform arrangement.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The frequency of each feature in melanoma was reported to be approximately 50%. 5,7,10,12,13 We found that these features were noted less frequently in the spindle cell melanomas (22%, 35%, and 22%, respectively), and 7 of the current study cases (9%) failed to exhibit any of the characteristic features. In addition, the cells of spindle cell melanoma tended to form cohesive microtissue fragments with a fascicular or storiform arrangement.…”
Section: Discussionmentioning
confidence: 81%
“…Perry et al 5 reported that pleomorphism was more frequent in epithelioid melanoma, whereas bland nuclei and inconspicuous nucleoli were far more frequent in spindle cell melanoma. Similarly, Nasiell et al 13 found that cytoplasmic melanin pigmentation, vacuolization, nucleoli, and intranuclear pseudoinclusions were observed less frequently in spindle cell melanoma compared with conventional melanoma. FNA specimens of metastatic spindle cell melanomas aspirated from various anatomic sites could be mistaken for metastatic lesions from other neoplasms or reactive lesions with similar features, especially when a reliable clinical history is unavailable and the tumor cells are predominantly or ''purely'' spindle shaped without the characteristic features of melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations